Pengaruh Ukuran Perusahaan, Financial Leverage, dan Struktur Kepemilikan Terhadap Konservatisme Laba pada Perusahaan Non Keuangan Sektor Bahan Baku Tahun 2020-2024: Penelitian - Hosea Boy Karan Galingging; Farma Andiansyah; Gundahara (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The principle of accounting conservatism emphasizes two main points, namely recognizing losses that are likely to occur but do not apply if profits are present and the second point, from all accounting recognition methods, accountants are expected to choose the method with the smallest profit. The purpose of this study is to determine and analyze the Effect of Company Size, Financial Leverage, and Ownership Structure on Profit Conservatism in Non-Financial Companies in the Raw Materials Sector in 2020-2024. The type of data used in this study is quantitative data with secondary data sources, namely from company financial reports. The collected data were tested using SPSS software consisting of descriptive statistical tests, classical assumption tests, multiple linear regressions, and simultaneous and partial hypothesis tests and coefficients of determination. Company Size partially has a negative and insignificant effect on Profit Conservatism. Financial Leverage partially has a positive and significant effect on Profit Conservatism. Ownership Structure partially has a positive and significant effect on Profit Conservatism. Leverage and Ownership Structure simultaneously have a positive and significant effect on Profit Conservatism in the Non-Financial Raw Materials Sector in 2020-2024. In the determination coefficient, the Adjusted R2 value obtained is 18.4%, meaning that variations in the variables of Company Size, Financial Leverage, and Ownership Structure can explain their effect on Profit Conservatism by 18.4%, while the remaining 81.6% is a variation of other variables not explained in this study, such as cash flow, etc.